Pengaruh Iklim Organisasi Terhadap Tingkat Kepercayaan Organsasi Di Universitas Swasta X Di Gresik - Idha Rahayuningsih (Jurnal Manajerial, 2020)
Background – The dynamics of the organization have an impact on positive and negative experiences for individuals which causes a decrease in trust among members of the organization. This efforts to foster trust in organizations need to be done through creating a participatory organizational climate. Purpose – Research to prove the influence of organizational climate on the Level of Organizational Trust in Private University X in Gresik. Design/ Methodology/ Approach – Type of quantitative research with a correlational level of analysis. The dependent variable is the Level of Organizational Confidence (Y), while the independent variable is the organizational climate. The study population was structural officials with saturated sampling techniques totaling 64 people. The data collection technique of the two variables is using a Likert scale with five answer choices. The instrument validity uses logical validity while the reliability coefficient is calculated by the Cronbach Alpha formula. The reliability coefficient of the Organizational Trust Scale is 0.937 while the Organizational Climate Scale is 0.912. Result and Discussion – Data analysis used simple regression statistical techniques with a significance level of 5%. Statistical test results with SPSS 14.00 resulted in a value of r = 0.460 and a value of F = 16,685 with a significance level of p = 0,000 <0.05, which means significant. Conclusion – There is a Significant Effect of Organizational Climate on the Level of Organizational Confidence in Private University X in Gresik. The effective contribution of Organizational Climate to the Level of Organizational Trust is 21.2% while 78.8% is influenced by other variables. Research Implication – Develop a participatory organizational climate to build trust in organizations. Research limitation - This research was only conducted at a University X in Gresik, with structural official respondents so that further research was needed to expand the population.